Hand Surgery in Cambodia - Rajaratnam, Vaikunthan; Rahman, Norana Abdul; Kim, Yong-June; Lam, Wee Leon; Gollogly, James (Journal of Hand and Microsurgery, 2020)
As a lower middle-income nation, Cambodia has made significant improvements in basic health but hand surgery development continues to lag behind due to scarcity of trained and quality surgical manpower. Most of the hand surgery development locally has been due to surgical volunteers from Asia, Europe, and the United States. The introduction of a structured and systematic community-oriented hand surgery training over a 5-year period was successful in producing local surgeons to meet the basic needs of hand surgery patients. Brachial plexus surgery has benefited significantly, with local surgeons able to independently manage cases with minimal support. With the expansion of local surgical manpower and guidance, motivation, and assistance of regional hand surgeons, the future of hand surgery in Cambodia looks promising.
Keywords: hand surgery; Cambodia; surgical volunteerism; hand surgery training; open educational resource; online learning